2020
DOI: 10.1161/circulationaha.120.050771
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine in Patients With Acute Coronary Syndrome

Abstract: Background: Inflammation plays a crucial role in clinical manifestations and complications of acute coronary syndromes (ACS). Colchicine, a commonly used treatment for gout, has recently emerged as a novel therapeutic option in cardiovascular medicine owing to its anti-inflammatory properties. We sought to determine the potential usefulness of colchicine treatment in patients with ACS. Methods: This was a multicenter, randomized, double-blind, placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(60 citation statements)
references
References 26 publications
1
56
0
3
Order By: Relevance
“…The proportion of patients with hypertension (46%) and diabetes (20%) was similar across all trials. Previous MI (15%) was also similar in three trials (20,21,23). The sample size (32-4,745 patients) and the length of follow-up (5 days−22.6 months) were heterogeneous across studies.…”
Section: Study Characteristicsmentioning
confidence: 87%
See 1 more Smart Citation
“…The proportion of patients with hypertension (46%) and diabetes (20%) was similar across all trials. Previous MI (15%) was also similar in three trials (20,21,23). The sample size (32-4,745 patients) and the length of follow-up (5 days−22.6 months) were heterogeneous across studies.…”
Section: Study Characteristicsmentioning
confidence: 87%
“…The most frequently reported gastrointestinal adverse events were nausea, vomiting, and diarrhea. The three trials (18,19,23) that provided information on myelotoxicity found no cases in both groups.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The result from the COPS clinical trial, a multicenter, randomized, double-blind, placebo-controlled trial published on August 29, 2020, that showed the addition of colchicine to standard medical therapy did not significantly affect cardiovascular outcomes at 12 months in acute coronary syndrome (ACS) patients and was associated with a higher rate of mortality (29). Over the 12-month follow-up, there were 24 events in the colchicine group compared with 38 events in the placebo group experiencing the event (p = 0.09, logrank).…”
Section: Anti-inflammatory Effects Of Colchicine In Atherosclerotic Heart Disease Need Further Evaluationmentioning
confidence: 99%
“…The findings of the COLCOT trial appear to be in conflict with the Australian COPS trial, a multicenter, randomized, double-blind, placebo-controlled trial [37] that enrolled 795 patients adult patients with acute coronary syndrome (ACS). In that study, 396 patients received colchicine (0.5 mg twice daily for the first month, then 0.5 mg daily for 11 months) and 399 received a placebo.…”
Section: Pathophysiology Of Ami-related Systemic Inflammation and Thementioning
confidence: 99%